Challenges in the diagmosis of cervical pathologies - D. Y. Chernov; O. A. Tikhonovskaya; S. V. Logvinov; I. A. Petrov; Y. S. Yuriev; A. A. Zhdankina; A. V. Gerasimov; I. V. Zingalyuk; G. A. Mikheenko (Бюллетень сибирской медицины)
This review deals with the current state of affairs in the diagnosis of cervical squamous intraepithelial lesions. Transformation of classifications of cervical pathologies is considered. The role of cytological (liquid-based and conventional cytology), molecular biological (Digene Hybrid Capture test), immunohistochemical (p16INK4α, Ki-67), and histologic methods in the diagnosis of cervical lesions is discussed. Particular attention is paid to the diagnosis of human papillomavirus infection. Performance indicators of screening programs based on primary determination of human papillomavirus (HPV) DNA in comparison with common cytological methods are presented. Tropism of HPV to various parts of the cervix, which predisposes to the formation of deep multifocal lesions, as well as the influence of the physical status of HPV on the treatment strategy and risks of relapse are considered.